Penggunaan Video Animasi untuk Meningkatkan Pengetahuan dan Kesadaran Siswa Sekolah Dasar Terhadap Perundungan - Anisa Fiola Karimah; Julia Julia; Prana Dwija Iswara; Ali Ismail; Diah Gusrayani; Isrokatun Isrokatun (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Bullying is a problem that can occur in educational settings. The existence of bullying in primary education can be the seed of other forms of violence. The role of educators in schools is needed in an effort to reduce the number of bullying through various strategies. This study aims to determine the effect of using character education-based animated videos on students' understanding based on two aspects, namely knowledge and awareness of bullying. The research subjects were high school students in Sumedang Regency. This study used a quantitative approach with a one group pretest-posttest design. The data collection instrument was a test administered to 96 students to measure the level of knowledge and awareness about bullying. The results of the paired t-test showed that the knowledge aspect obtained a value of p<0.05 (0.00<0.05) and the awareness aspect obtained a value of p<0.05 (0.00<0.05), meaning that there was a difference between the average score of the pre-test and post-test scores from the knowledge and awareness aspects. The use of character education-based animated videos significantly improved the knowledge and awareness of high school students towards bullying behavior.